(untitled) (Global Journal of Human-Social Science, 2021)
Treated water represents a real alternative to reduce the global freshwater crisis However management approaches are applied that depart from the linear thinking of producing consuming and discarding In this sense the circular economy is an option to generate products that from their origin are oriented to be reused In this way if we think about treated water from this conceptual framework we would mitigate water scarcity in cities The effluent generated in the Las Joyas Wastewater Treatment Plant was evaluated in the survival development and cultivation of Oreochromis niloticus 350 adult tilapia specimens were sown 50 females and 300 males The effluent will achieve the survival development and cultivation of tilapia